On Residual Properties of Nilpotent Groups - P.C, Wong; K.B2, Wong (Malaysian Journal of Science, 2005)
In this note we will investigate the conjugacy separability and cyclic conjugacy separability of extensions of finitely generated nilpotent groups. We then apply our results to give new proofs that finite extensions of finitely generated nilpotent group are conjugacy separable and cyclic conjugacy separable.